Pastoralité in eastern Turkey - Michaël Thevenin (Revue de Géographie Alpine)
In this article, we will confront the pastoral practices of the Kurdish populations in eastern Turkey, which is a very ancient culture, to the heritage process in order to try to establish a pastoralité, a concept emerging in the French academic circles. Pastoral practices in eastern Turkey are characterised, like high mountains (pasture) shelters, by a great diversity due to geographical, historical and social contexts, but also to the recent establishment of the Turkish nation-state and Kurdish nationalism, the most striking trait of which is the persistence of tribal allegiance. We are witnessing an impossible standardisation of these practices and a heritage institutionalisation, although one that remains hypothetical considering how the different forces in presence play out. Stuck between three settings of representation - that of pastoral communities, those of Turkish or Kurdish nationalisms and those inherent to the internal logic of the heritage institutionalisation - pastoralism in the Anatolian East could be understood as a pastoralité defined as a resisting community, the territory being itself an actor of this resistance. In this form, the pastoralité would be an identitary construction. We would like to offer another reading, closer to a tool than to an ideology, and which can encompass both the geopolitical complexity of the Turkish land and what is at stake for the French: pastoralité could firstly be a pastoral concept and a resilience as well as a transformation field.